2021
DOI: 10.9734/ijpss/2021/v33i1830590
|View full text |Cite
|
Sign up to set email alerts
|

Ions and Organic Solutes as Implicated in the Ameliorative Effect of Exogenous Application of Calcium on Salt Stressed Tomato (Lycopersicon esculentum Mill.) Plants

Abstract: Aims: This study evaluated the role of sodium, potassium, proline and soluble sugars accumulation in the ameliorative effect of an exogenous application of calcium on the detrimental effect of salinity on tomato plants. Study Design: The experiment was implemented as a Completely Randomized Design (RCD) with four treatments and three replications. Place and Duration of Study: The experiment was realized in a green house of the Faculty of Agronomical Sciences, University of Abomey-Calavi, Benin Repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 44 publications
(68 reference statements)
1
6
0
Order By: Relevance
“…The same tendency was reported in leaves of African basil plants [13]. However, salt stress effect generally resulted in a reduction in K + content as reported in several vegetable species such as sweet basil [24], eggplant [25] ; okra [26,27] ; African basil [13] ; tomato [14] and tossa jute [28].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…The same tendency was reported in leaves of African basil plants [13]. However, salt stress effect generally resulted in a reduction in K + content as reported in several vegetable species such as sweet basil [24], eggplant [25] ; okra [26,27] ; African basil [13] ; tomato [14] and tossa jute [28].…”
Section: Discussionsupporting
confidence: 76%
“…Na + and K + extraction and quantification were done from leaf and root dry matters as described by [14] using a flame spectrophotometer (Sherwood Model 360). Ions were expressed in mg g -1 dry matter (dm).…”
Section: Extraction and Measurement Of Ion Concentrationsmentioning
confidence: 99%
See 1 more Smart Citation
“…To mitigate the effects of salt stress, exogenous Ca management is vital. Exogenous calcium has also been shown in several previous studies to mitigate salt stress in tomato by osmotic adjustment, an increase in antioxidant enzyme activities, the accumulation of sodium, potassium, and proline, as well as through enhancing the formation of roots and shoots [29][30][31]. It increases tolerance to salt stress by modifying growth performance, photosynthetic effectiveness, and stress-induced ROS metabolism [32,33].…”
mentioning
confidence: 95%
“…Therefore, exogenous application of Ca is an important method to overcome the salt stress. Several previous studies also reported that exogenous calcium mitigates salt stress in tomato by osmotic adjustment, increasing antioxidant enzyme activities and the accumulation of sodium, potassium, proline and by enhancing root and shoot formation [ 27 , 28 , 29 ]. However, many aspects of exogenous Ca-mediated salt tolerance in tomato remain elusive.…”
Section: Introductionmentioning
confidence: 99%